O papel do receptor 1 do TNF na infecção por Leishmania amazonensis: promoção e regulação da inflamação - Leonardo Gomes Vaz (2016)
The Th1/Th2 paradigm that explains most models of infection with Leishmania major does not apply to the experimental models of infection with L. amazonensis. In this latter model, mixed immunological responses rather than polarization are observed, in contrast with the Th1/Th2 paradigm of resistance and susceptibility. TNF is a pleiotropic cytokine that mediates inflammation, lymphoid tissue development and homeostasis, extracellular matrix destruction, among other functions. TNF binds to two receptors, TNFR1 and TNFR2. Both receptors trigger inflammatory responses but only by binding to TNFR1 TNF mediates regulation or supression of inflammation, through induction of apoptosis via caspase 8/3. Hence, our work aimed at the identification of the role of TNFR1 the mouse model of infection with L. amazonensis. Our data reveal the importance of TNFR1 in the control of lesion development, but not on the control of parasite replication. This control was more efficient in the subcutaneous model of infection where, in addition to promoting lesion control, TNFR1 was importante in the maintainance of tissue homeostasis, probably due to IL-10 production. Furthermore, in the accute phase of the subcutaneous infection, TNFR1 mediated recruitment of mieloid cells and lymphocytes to the site of infection and, in the chronic phase, regulated cell recruitment. TNFR1-mediated apoptosis was inhibited during intradermic infection by L. amazonensis, and an alternative pathway was in play. However, our data indicate that apoptosis seems to be inhibited by the pro-inflammatory signaling through TNFR1, since apoptosis was lesser in wild-type mice. In conclusion, our data suggest the involvement of TNFR1 in resistance to L. amazonensis. This conclusion is supported by the fact that TNFR1 acts both in the promotion and in the regulation of inflammation. Regulation is crucial for preservation of the infected tissue, and seems to be related to continuous production of IL-10, observed mainly in the subcutaneous infection. The two different routes of infection evolve into diferente types of responses: the intradermic route the lack of control of necrosis is associated to massive tissue loss, while the subcutaneous route control of cell recruitment preserves the affected tissue.